Fierce love : a memoir of family, faith, and purpose - Curry, Sonya; Eisenstock, Alan (HarperOne, an imprint of HarperCollinsPublishers, 2022)
Sonya Curry chronicles the never-before-shared story of raising her children and her lifelong devotion to education, family, and faith. Like her superstar sons' and extraordinary daughter's, Sonya Curry's journey was filled with defeats and hard-fought victories, but hers took place out of the limelight, without the eyes of the world watching, cheering, or drawing inspiration from her example. Until now. In this inspiring memoir, Curry tells her story for the first time, beginning with her childhood in rural Virginia and moving through the peaks and valleys of an incredible life--from raising her immensely gifted but sometimes headstrong children, to becoming an educator and founding a Montessori school, to discovering a profound, life sustaining connection to God and faith. Fierce Love, a wise and illuminating story of family, faith, and purpose, is sure to become a classic. With something for everyone--seekers, sports fans, people of faith, lovers of memoir-- it's one strong mother's gift to all who wonder how, where, and whether they'll find the strength.